Hemodynamic changes and autonomic nervous system after acute myocardial infarction in rats submitted to left coronary artery ligation - Nascimento, Daniela Meirelles; Schaan, Beatriz D’Agord; Belló-Klein, Adriane; Dal Lago, Pedro; Irigoyen, Maria Cláudia (Clinical and Biomedical Research, 2018)
Introduction: Heart failure is a clinical syndrome characterized by sympathetic/ renin-angiotensin system activation, besides parasympathetic activity attenuation. In the initial phase of HF, following a myocardial infarction, there is impairment of the ventricular function and this can be influenced by the myocardium ischemia area in addition to alteration in the autonomic control of the heart. The aim of this study is to evaluate the hemodynamic responses and autonomic nervous system and its associations in infarcted rats by left coronary artery ligation. Methods: Forty male rats were submitted to left coronary artery ligation: infarcted animals with fifteen days from cardiac surgery (I15), infarcted animals with thirty days from cardiac surgery (I30) and sham-operated groups (S15 and S30), with 10 animals in each group. Basal hemodynamic data and heart rate variability (spectral analysis) were evaluated. Results: Compared to control groups, the infarcted rats demonstrated the following complications: a) cardiac hypertrophy (I30); b) pulmonary congestion (I30); c) mean arterial pressure (MAP), systolic arterial pressure (SAP) and diastolic arterial pressure (DAP) reduction; d) left ventricular systolic pressure (LVSP) reduction and left ventricular end-diastolic pressure (LVEDP) rise; e) contractile (+dP/dt) and relaxation derivatives (-dP/dt) reduction; f) sympathetic cardiac activity increase, and parasympathetic cardiac activity reduction (I30). Conclusion: Our study shows that the infarcted animals presented left ventricular dysfunction, which was influenced by the infarct size. In addition, impairment of autonomic control was present only in the animals belonging to the I30 group, probably due to the degree of cardiac decompensation and disease progression. Keywords: Heart failure; myocardial infarction; heart rate variability